Dwelling in the Urban Liminal: A Phenomenological Consideration of Saul Leiter’s Street Photography - Satarupa Sinha Roy (Text Matters, 2024)
In this essay, I present a phenomenological exploration of the “urban liminal” in the context of Saul Leiter’s street photography. In gauging the possibilities of dwelling in the urban liminal, this essay brings into dialogue Heidegger’s notion of “wohnen” (as delineated in “Building, Dwelling, Thinking”) and Leiter’s re-presentation of liminal places (and liminality). As transient spatialities, liminal places are not typically considered suitable for dwelling, meaning living or settling. But as neither space nor time is immutable and is always—whether evident or not—in a constant state of flux, it is useful to re-assess and re-imagine from time to time our relationship with place (and time) and, in the process, to reappraise the questions of identity and belongingness. In its investigation of the latencies of liminal places in Leiter’s street photography, this essay poses questions such as: is it possible to dwell (or be at home) in liminalities? How might the visual representation of liminality help deepen our understanding of transitional states and of change? How does Leiter’s stylization of liminality connect with our lived experience of these places? By examining Leiter’s depiction of urban liminality from a phenomenological perspective, this essay aims to show how liminality can be a useful concept for reimagining the relationship between the self and the world.